Are cancer survivors well‐performing workers? A systematic review. Issue 4 (20th July 2016) - Soejima, Takafumi; Kamibeppu, Kiyoko
Abstract: Cancer, its therapy, and related adverse effects have been associated with reduced work performance, including absenteeism (i.e. absence from scheduled work due to health problems) and presenteeism (i.e. impaired on‐the‐job performance due to health problems) among cancer survivors. This review aimed to compare the work performance of employed cancer survivors with that of cancer‐free controls, and to examine factors related to the impairment of work performance. The findings from this review could bring about suggestions for clinical interventions aimed at improving survivors' work performance. Literature searches on cancer survivors' work performance were conducted in three electronic databases (MEDLINE, CINAHL and PsycINFO). Twenty‐six studies were identified. Most studies comprised survivors of breast, prostate, testicular and gastrointestinal cancer. Although survivors diagnosed within 5 years reported more absenteeism than did controls in the studies, there was no difference between controls and survivors diagnosed >5 years earlier. Survivors diagnosed within 5 years also reported more presenteeism than did controls. Many studies reported that the complications related to cancer and its therapy (e.g. fatigue and depression) were associated with presenteeism. A multifaceted intervention for the various factors identified in this review would contribute towards improved work performance among employed cancer survivors.